Political ecology and critical geography of waste in Ecuador - Solíz Torres, María Fernanda (2015)
Ecuador produces 58.829 tons of solid waste weekly. Only 20% is disposed on appropriate conditions, the remaining percentage is distributed between open dumps, controlled landfills, rivers and incinerators. The 45,5% of municipalities reports the presence of informal recyclers, and it is estimated that the total recycling rate (formal and informal) is 14%. From a vision of political ecology, the article proposes a national diagnostic conducted during the years 2010-2012 through structured interviews and fieldwork in each of disposal systems. The article expects to highlight the structure and determination of double crises (qualitative and quantitative) of trash in Ecuador.